Effectiveness of manual therapy for patients with low back pain from the perspective of physical and psychosocial factors - Hattori, Hiroshi; Okubo, Yu; Kikuchi, Yuto; Hamada, Yuji; Mizoguchi, Yasuaki; Akasaka, Kiyokazu; Nakagawa, Hotaka (Journal of Physical Therapy Science, 2024)
[Purpose] This study aimed to determine the effectiveness of the Arthrokinematic Approach (AKA)-Hakata method for patients with low back pain (LBP). [Participants and Methods] The participants were 39 patients with LBP who visited a medical facility between June 1, 2022, and November 30, 2022. The intervention period was 8 weeks, with five treatment sessions, and the patient assessments were performed using patient self-reported measures of LBP and motor function assessment. [Results] The AKA-Hakata method showed significant differences in all of the items evaluated in the longitudinal comparison of patients. Additionally, an interaction was observed only in the Roland-Morris Disability Questionnaire between the two groups classified using the Subgrouping for Targeted Treatment Back Screening Tool. [Conclusion] The results of this study showed that treatment with the AKA-Hakata method may have an early therapeutic effect on the physical and psychosocial risks in daily life. The results of this study indicated that the AKA-Hakata method is effective for the treatment of LBP. However, this study only evaluated a relatively short treatment period of five sessions. Further research on the long-term treatment effect is needed in order to optimize the treatment duration in detail and investigate the effectiveness of the AKA-Hakata method.